Does Pregnenolone Enhance Exposure Therapy in Obsessive-Compulsive Disorder? – A Pilot, Interim Report of a Randomized, Placebo-Controlled, Double-Blind Study - Kellner, M.; Nowack, S.; Wortmann, V.; Yassouridis, A.; Wiedemann, K. (Pharmacopsychiatry, 2016)
Exposure therapy is an effective cognitive-behavioral treatment for patients with obsessive-compulsive disorder (OCD). However, a further amelioration of symptoms by additional drugs that enhance extinction learning is desirable. An interesting candidate is pregnenolone, which positively modulates NMDA and GABAA receptors in preclinical studies and influences amygdala and prefrontal activity in humans. We present pilot data showing high acceptance and good tolerability of pregnenolone given 2 h before exposure sessions in OCD patients. As per our interim analyses, exposure treatment resulted in significantly improved main outcome parameters, but no effects of pregnenolone vs. placebo pretreatment were detectable thus far.
Keywords: pregnenolone; obsessive-compulsive disorder (OCD); exposure therapy